Leverage actually: The impact on banks' borrowing costs in euro area money markets - Desislava Andreeva; Anna Samarina; Lara Sousa Faria (European Central Bank (ECB), 2025)
This paper explores the impact of the regulatory leverage ratio (LR) on banks' demand for reserves and thus the pricing of overnight liquidity in the euro area money markets. We use daily transaction-level money market data during the period between January 2017 - February 2023 and examine the two major overnight money market segments - the unsecured and the secured one, distinguishing between over-the-counter (OTC) and CCP-cleared trades for the latter. We find a significant positive link between a bank's LR and the spread between its money market borrowing rate and the DFR. Banks with a higher LR offer deposits at higher interest rates, thereby reducing the markdown vis-à-vis the DFR. The impact of the LR dampens during the period in which central bank reserves did not count towards the LR exposure measure (or the denominator of the ratio). It is stronger for G-SIBs, who need to comply with a G-SIB LR add-on on top of the minimum requirement applicable to all euro area banks. Moreover, the impact is weaker for CCP-cleared transactions compared to OTC trades, likely reflecting the possibility to net bilateral exposures if cleared via CCPs, which effectively allows banks to finance the respective gross money market exposures with a smaller share of Tier 1 capital.
Keywords: G12; G21; G28; 330; leverage ratio; money markets; exteuroSTR; bank balance sheet constraints